Cause of death to be established and sud den death: A matter of approach (2017)
Purpose: This article was prepared to raise awareness in the forensic field of the importance of clearly conceptualizing causes of death to be established by contributing different available articles, taking the most relevant aspects, and applying them to a real context. Period covered, origin and types of publications: A search was made in databases and in literature described in forensic books with relevant information about causes of deaths to be established, considering a period between 1908 and the present time, with themes related to sudden death in both the forensic and the clinical medical fields. Point of view: During a forensic investigation we face causes of death to be established, which often are the Achilles’ heel of forensic investigators; the conception and concept of cause of death to be established must be clear from the beginning of a case and even from the very scene one must be clear about how it should be approached and thus determine cause and manner of death holistically as a final context. Conclusions: Cause of death to be established is a type of death that must be addressed top-down on a solid basis, starting from the clear conception of the coroner who takes on the case, the approach with a methodology and progression in ordered steps detailed in the autopsy protocol, until drawing a conclusion.